Double Happiness and the Pin: Landscapes of Cultural Change and Spatial Instability Introduction - Droppo, Leah (Université d'Ottawa | University of Ottawa, 2018)
This article uses Carol O‘Sullivan‘s aural and visual storytelling and Northrop Frye‘s "obliterated environment" to relate how the language within the landscape problematizes the transference of cultural spaces through the medium of film. Mise-enscène is used as a an overarching term to stand in for the directors‘ focus on lighting, space, film-stock, acting, and camera composition. This article breaks down aural and visual representation of Chinese and Jewish cultures within the films to define the cultures‘ spaces of existence and question how they are transmitted within a Canadian context. Through Frye‘s question ―Where is here?‖, this paper is positioned to break down the space of storytelling to determine how the characters negotiate their hybridized identities beyond their homelands.
Keywords: Northrop Frye; Carol O‘Sullivan; cultural spaces; film